Hệ trợ giúp kê và kiểm tra đơn thuốc chữa bệnh tăng huyết áp es-tension - Thủy, Nguyễn Thanh (Journal of Computer Science and Cybernetics, 2016)
In this paper, we investigate some features of the ES-Tension system for supporting prescription and verification of therapy recommendation for the hypertensive disease. The system is implemented in Borland C, version 3.1 with the Knowlegde base of 234 rules. These  rules are devided into 4 subclasses. In addition to the reasoning capacity, ES-Tension can explain and  judge why and  how questions of non-professional users.